Sensitive cell-free tumor DNA analysis in supernatant pleural effusions supports therapy selection and disease monitoring of lung cancer patients. (2021) - de Kock, Remco; Knoops, Chantal; Baselmans, Mieke; Borne, Ben van den; Brunsveld, Luc; Scharnhorst, Volkher; Deiman, Birgit
Highlights: PE is a valuable source for ctDNA analysis to support therapy selection and disease monitoring. PE enables more sensitive ctDNA analysis compared to plasma. Longitudinal ctDNA analysis in PE better reflects the course of the disease and therapy response compared to plasma. Abstract: Supernatant pleural effusions (PE) have shown to be a valuable source for the detection of driver mutations in circulating tumor DNA (ctDNA). In this prospective study, the clinical value of ctDNA analysis in supernatant PE to support therapy selection and disease monitoring in lung cancer patients is assessed. Paired PE and plasma samples were collected from lung cancer patients before initiation of therapy ( N  = 2) and from EGFR positive patients during therapy ( N  = 3). Supernatant PE and plasma were tested for mutations in EGFR, KRAS and BRAF by droplet digital PCR . In PE of two patients with suspected lung cancer, a KRAS mutation was detected with a 5- and 8-fold higher fractional abundance (FA) compared to plasma. For three patients with progressive disease during therapy, both the EGFR L858R and T790M mutations were detected in PE. However, in plasma only for two of these patients the L858R mutation was detected with a 46- and 14- fold lower FA, and only for one patient the T790M mutation was detected with a 8-fold lower FA. For one patient, longitudinal ctDNA analysis in PE revealed the T790M and L858R mutations already two months prior to detection of progressive disease by CT-scan. In this study, a higher ctDNA concentration and FA was obtained from PE compared to the corresponding blood samples, which enables more sensitive mutation analysis. Thus, PE is a valuable liquid biopsy, complementing plasma, for ctDNA analysis to support therapy selection and disease monitoring in lung cancer patients.